Valuing preferences for changes in open-water space and water quality in the Kleinmond Estuary : a discrete choice experiment - Josias, Lauren Natania (Stellenbosch : Stellenbosch University, 2025)
Thesis (MPhil)--Stellenbosch University, 2024.